Pendidikan Keluarga Perspektif Tafsir Maudhui Dalam Al-Quran - Rendi Saputra; Ahmad Wahyu Hidayat; Achmad Farid (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2021)
Abstract: Family education is important as stated in the three primary education. This research is aimed to explore the concept of family education in the Quran. This research is a qualitative research and is a library research. The primary data is the Quranic verses related to the family education. The data has been collected using the documentation method. The data were collected and analyzed using the maudlui (thematic) interpretation approach. The results showed that family education in the Quran can thematically read through the husband's dutied to lead and look after the family, the wife's duties to obey her husband and give breastfeed her children until the age of two, and the child's duties to be filial and do not yell at their parents. Meanwhile, the method of family education in the Quran are the reading habits, good teaching methods, keep good talking, and discussion.